2005
DOI: 10.2174/1568010054022150
|View full text |Cite
|
Sign up to set email alerts
|

Pro and Antiinflammatory Properties of Toxins from Animal Venoms

Abstract: Accidents evoked by venomous animals are common in tropical regions. In Brazil, envenomation evoked by snakes, spiders and scorpions are an important public health problem. Their venoms are composed of a great number of toxins, which are capable of acting on tissue and plasma components with consequent toxic and pharmacological effects. On the other hand, the diversity of venom composition makes them important source of toxins that can be employed as scientific tools. Here we describe the mechanisms of anti an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 248 publications
(324 reference statements)
0
15
0
3
Order By: Relevance
“…Studies have shown that the Bothrops atrox venom peptide, batroxobin, caused a significant decrease in the fibrinogen level, whereas it had no effect on paw swelling [10] . Crotalus durissus terrificus venom, which contains crotoxin as a major active component, administered subcutaneously before or after subplantar injection of carrageenan into the mouse right hind paw significantly inhibited edema and migration of polymorphonuclear cells to the peritoneal cavity [11,12] . Cobra venoms contain high levels of neurotoxins that target nicotinic acetylcholine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the Bothrops atrox venom peptide, batroxobin, caused a significant decrease in the fibrinogen level, whereas it had no effect on paw swelling [10] . Crotalus durissus terrificus venom, which contains crotoxin as a major active component, administered subcutaneously before or after subplantar injection of carrageenan into the mouse right hind paw significantly inhibited edema and migration of polymorphonuclear cells to the peritoneal cavity [11,12] . Cobra venoms contain high levels of neurotoxins that target nicotinic acetylcholine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…IR has been used to study diseases in which skin temperature can reflect the presence of inflammation in underlying tissues, or those in which blood flow is increased or decreased because of a clinical abnormality 1,2 . It is widely known that animal venoms are capable of inducing localized reactions involving inflammation and pain 3 . One of the challenges that clinicians face when treating patients envenomed by venomous animals is a lack of suitable clinical tools for accurate assessment of the localized effects caused by different venoms in order to provide refined criteria for choosing the best therapeutic option, especially the most efficacious use of antivenom.…”
Section: Infrared Imaging (Ir) Is a Noninvasive Technique Thatmentioning
confidence: 99%
“…New applications for dendrimers open an exciting area for proteomics research that will provide a simple and effective alternative to currently available quantitative technologies. Snake venoms contain complex mixtures of secreted proteins belonging to many different classes such as neurotoxins, toxins, cardiotoxins, myotoxins, hemorrhagins, and disintegrins (17). These same proteins that cause tissue damage and trauma when animals or humans are envenomed are also of medical and pharmacological importance.…”
mentioning
confidence: 99%